Progressive Income Tax Structure and Its Effect on Income Inequality in Iranian Provinces - Mahnoush Abdollah Milani (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2017)
One of the important objectives of policymakers in a society is reduction of income inequality. Taxes, as source of stable income for government, are the most important tools for adjusting income inequality. An efficient tax system in the form of progressive taxation can lead to improved income distribution. This paper evaluates the impact of progressive income tax on income inequality in 30 provinces during the period 2005 - 2013 in Iran. For this purpose, the average income tax rate is calculated for each income decile and its effect on Gini coefficient has been tested while controlling for other independent variables which include the share of services and industry sectors in GDP and per capita income growth in each province. The empirical method of this study was based on panel data approach for which we applied Generalized Method of Moments (GMM) to estimate the dynamic equation. The results show that although the income tax is progressive in Iran, but the tax system has failed to reduce income inequality.